PENGARUH JARAK TANAM DAN GULMA TERHADAP HASIL TANAMAN JAGUNG MANIS (Zea mays L. Saccharata Sturt) - Badrul Ainy Dalimunthe (JURNAL AGROPLASMA, 2019)
Sweet corn is one of the commodity crops that can take part in the development of agriculture weed is a plant that no wants to grow. The presence of weed in the corn plants causes the plant productivity down. The research aims to know the effects of growing distances and weeds on the produce of sweet corn. This study was carried out in the village of Asam Jawa, Torgamba sub-district, South Labuhanbatu Regency in January until March 2018. The design used is the randomized design of the group. There are three diffrent types of plant distances that are 75 cm x 25 cm, 50 cm x 25 cm, 50 cm x 25 cm with a combination of treatment without broadcast,it is spent 7 days after planting, 14 days after palnting, 21 days after growing and clean investigation during research.The number of deuteronomy consists of 3 and each of the deuteronomy consists of 73 plants and file obtained by the method of rate. The research has shown that the high plants highest plant is found at 60 cm x 25 cm (J2) and the lowest found at 50 cm x 25 cm (J3). The number of leaves are much the same in every plants distances. The largest diameter of the stems is foud at 60 cm x 25 cm (J2) and a small diameter of the smallest stick is found at 50 cm x 25 cm (J3). The biggest weed is gained at a distance of 75 cm x 25 cm (J1) and the size of the smallest weed is foud at 50 cm x 25 cm (J3). The largest yields of corn comes at a distance of 60 cm x 25 cm (J2) and the least amount of corn is found at a distance of 50 cm x 25 cm (J3). Keywords : growing distance, sweet corn, weed